The Knockout for G Protein-Coupled Receptor-Like PfSR25 Increases the Susceptibility of Malaria Parasites to the Antimalarials Lumefantrine and Piperaquine but Not to Medicine for Malaria Venture Compounds - Santos, Benedito M.; Dias, Bárbara K. M.; Nakabashi, Myna; Garcia, Celia R. S. (Frontiers in Microbiology, 2021)
Previously we have reported that the GPCR-like receptor PfSR25 in Plasmodium falciparum is a K+ sensor linked to intracellular calcium signaling and that knockout parasites (PfSR25-) are more susceptible to oxidative stress and antimalarial compounds. Here, we explore the potential role of PfSR25 in susceptibility to the antimalarial compounds atovaquone, chloroquine, dihydroartemisinin, lumefantrine, mefloquine, piperaquine, primaquine and pyrimethamine and the Medicine for Malaria Venture (MMV) compounds previously described to act on egress/invasion (MMV006429, MMV396715, MMV019127, MMV665874, MMV665878, MMV665785 and MMV66583) through comparative assays with PfSR25- and 3D7 parasite strains. The assays were performed using flow cytometry with parasites stained with a double label method, using SYBR Green I and MitoTracker Deep Red. The IC50 and IC90 results show that lumefantrine and piperaquine have a greater impact on the PfSR25- parasite strain when compared to 3D7, suggesting that PfSR25 may be part of the mechanism that leads to parasite resistance to the antimalarials lumefantrine and piperaquine. For MMV compounds, we found no differences between the strains except for the compound MMV665831 which we used to investigate the store-operated calcium entry (SOCE) mechanism. Our data clearly show that MMV665831 does not affect calcium entry in parasites after we depleted their internal calcium pools with thapsigargin. The classical SOCE assay with 3D7 and PfSR25- parasites in the presence of MMV665831 indicated that the parasite must rely on the generation of other secondary messengers such as cGMP and cAMP for the signaling processes involved in parasite egress and invasion.